COMPARISON OF THE TIME OF SIMPLE REACTION BETWEEN CENTRAL ATTACKERS AND OPPOSITE ATTACKERS OF MASCULINE ADULT VOLLEYBALL (Fiep Bulletin - online, 2011)
The volleyball can be defined as a sport situational, for requesting great adaptation capacity to the variables that modify continually. In agreement with the specificity related to it responsibility, during the own technical training the athlete is constantly submitted to situations that can help you to obtain faster answers. The objective of this study was of comparing the scores of the time of simple reaction among players of masculine volleyball, who are responsible for the execution of different functions inside of the team. N=18 athletes were analyzed, being: 10 central attackers (mean of age = 23±2,62 years) and 8 opposed attackers (mean age 25,7±7,57 years). All of the athletes participated in the final phase of JAI (Games Open of the Interior), accomplished in Campos of Goytacazes-Rj. As result, was obtained the descriptive statistics and the inferential through the test "t" for independent samples: Central attackers: 269,06±54,76 ts; Opposed Attackers: 285,48±82,36 ts. We found a significant difference between groups p=0,00 (p
Keywords: Volleyball; Reaction of Time and Specificity